2023
DOI: 10.1186/s12888-023-04683-2
|View full text |Cite
|
Sign up to set email alerts
|

Hypnotic prescription trends and patterns for the treatment of insomnia in Japan: analysis of a nationwide Japanese claims database

Abstract: Background There is limited consensus regarding the optimal treatment of insomnia. The recent introduction of orexin receptor antagonists (ORA) has increased the available treatment options. However, the prescribing patterns of hypnotics in Japan have not been comprehensively assessed. We performed analyses of a claims database to investigate the real-world use of hypnotics for treating insomnia in Japan. Methods Data were retrieved for outpatients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Additionally, network meta‐analysis revealed that lemborexant was the best profile from the aspects of efficacy, acceptability, tolerability, and safety 2 . Therefore, the proportions of patients with insomnia receiving ORA has been increasing from 0% in 2013 to 20% in 2019 3 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, network meta‐analysis revealed that lemborexant was the best profile from the aspects of efficacy, acceptability, tolerability, and safety 2 . Therefore, the proportions of patients with insomnia receiving ORA has been increasing from 0% in 2013 to 20% in 2019 3 …”
Section: Discussionmentioning
confidence: 99%
“…Second, it may reflect changes in the prescription of hypnotic medications over time. A study using the Japanese clime database reported a significant decrease in BZA and an increase in ORA from 2010 to 2019 [ 17 ]. However, this study took this into account and adjusted for the year in which the data were obtained as a covariate.…”
Section: Discussionmentioning
confidence: 99%
“…First, the types of hypnotic medications used in clinical practice have changed over time. Recently, orexin receptor antagonists (ORA), which are novel hypnotic medications with novel mechanisms of action, have been developed, and studies using large Japanese databases have shown that the types of hypnotic medications used have changed significantly [ 17 , 18 ]. The second is the recent reform of the reimbursement system for prescribing hypnotic medications.…”
Section: Introductionmentioning
confidence: 99%
“…Whether the participants’ prescribing trends reflect the broader medical situation remains unclear, as there are no studies on the actual prescribing of sleep medications in Japan for 2022, when this survey was conducted. A pharmacoepidemiologic study using a nationwide Japanese claims database reported that between 2010 and 2019, benzodiazepine prescriptions decreased from 54.8% to 30.5%, MRAs increased slightly from 3.2% to 6.3%, ORAs increased significantly from 0% to 20.2%, and Z-drugs remained stable at approximately 40% [ 32 ]. Considering prescribing trends in the previous study [ 32 ], Japanese primary care physicians seem to prefer novel sleep medications.…”
Section: Discussionmentioning
confidence: 99%
“…A pharmacoepidemiologic study using a nationwide Japanese claims database reported that between 2010 and 2019, benzodiazepine prescriptions decreased from 54.8% to 30.5%, MRAs increased slightly from 3.2% to 6.3%, ORAs increased significantly from 0% to 20.2%, and Z-drugs remained stable at approximately 40% [ 32 ]. Considering prescribing trends in the previous study [ 32 ], Japanese primary care physicians seem to prefer novel sleep medications. The results of this study on ORAs align with those of a systematic review and network meta-analysis (NMA) published in 2023 by Yue et al [ 31 ].…”
Section: Discussionmentioning
confidence: 99%